2010
DOI: 10.1007/s10514-010-9207-y
|View full text |Cite
|
Sign up to set email alerts
|

Observability-based consistent EKF estimators for multi-robot cooperative localization

Abstract: In this paper, we investigate the consistency of extended Kalman filter (EKF)-based cooperative localization (CL) from the perspective of observability. We analytically show that the error-state system model employed in the standard EKF-based CL always has an observable subspace of higher dimension than that of the actual nonlinear CL system. This results in unjustified reduction of the EKF covariance estimates in directions of the state space where no information is available, and thus leads to inconsistency.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
53
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 94 publications
(55 citation statements)
references
References 38 publications
2
53
0
Order By: Relevance
“…The work by Huang et al [11,12,13] was the first to identify this connection for several 2D localization problems (i.e., simultaneous localization and mapping, cooperative localization). The authors showed that, for these problems, a mismatch exists between the number of unobservable directions of the true nonlinear system and the linearized system used for estimation purposes.…”
Section: Related Workmentioning
confidence: 99%
“…The work by Huang et al [11,12,13] was the first to identify this connection for several 2D localization problems (i.e., simultaneous localization and mapping, cooperative localization). The authors showed that, for these problems, a mismatch exists between the number of unobservable directions of the true nonlinear system and the linearized system used for estimation purposes.…”
Section: Related Workmentioning
confidence: 99%
“…It should be noted that even though a rich body of literature on observability analysis for SLAM or CL (e.g., see [30][31][32][33][34][35][36]), to the best of our knowledge, no prior work has examined the parameter observability for the CLATT system. The study of parameter observability examines whether the information provided by the available measurements is sufficient for estimating the parameters without ambiguity; when parameter observability holds, the Fisher information matrix (FIM) is invertible [25].…”
Section: Observability Analysismentioning
confidence: 99%
“…Since the sufficient dead-reckoning condition (12) can only ensure local observability rather than global one, some trajectories of RF and beacon are not distinguishable using a single static beacon as shown in Fig. 1.…”
Section: B Observability Analysismentioning
confidence: 99%
“…In [10]- [12], the rank of an observability matrix is used for observability analysis of linear systems or linearized nonlinear systems. But the original localization systems are usually non-linear and the linearization may cause wrong decision to observability [3].…”
Section: Introductionmentioning
confidence: 99%